2020
DOI: 10.1038/s41467-020-16851-z
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal lymphatics clear erythrocytes that arise from subarachnoid hemorrhage

Abstract: Extravasated erythrocytes in cerebrospinal fluid (CSF) critically contribute to the pathogenesis of subarachnoid hemorrhage (SAH). Meningeal lymphatics have been reported to drain macromolecules and immune cells from CSF into cervical lymph nodes (CLNs). However, whether meningeal lymphatics are involved in clearing extravasated erythrocytes in CSF after SAH remains unclear. Here we show that a markedly higher number of erythrocytes are accumulated in the lymphatics of CLNs and meningeal lymphatics after SAH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(164 citation statements)
references
References 54 publications
11
127
1
Order By: Relevance
“…These results provide strong support for the old theory of RBCs evacuation from the brain via lymphatic efflux [12][13][14][15][16][17]. Our data are also consistent with the newest discovery of the meningeal lymphatic pathway of clearance of RCBs from the brain after brain hemorrhage [25,26]. Taking into account all of the above, we hypothesized that the lymphatic mechanisms of blood clearance from the brain can be a new therapeutic target for treatment of IVH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results provide strong support for the old theory of RBCs evacuation from the brain via lymphatic efflux [12][13][14][15][16][17]. Our data are also consistent with the newest discovery of the meningeal lymphatic pathway of clearance of RCBs from the brain after brain hemorrhage [25,26]. Taking into account all of the above, we hypothesized that the lymphatic mechanisms of blood clearance from the brain can be a new therapeutic target for treatment of IVH.…”
Section: Discussionsupporting
confidence: 90%
“…Quite recently the old concept of lymphatic pathway of RBC move from the brain was supplemented by new knowledge of RBCs clearance via the meningeal lymphatic vessels (MLVs) after ICH that was first proposed by our group in 2019 [25] and afterward it was studied after SAH by Chinese group in 2020 [26]. However, it still remain unanswered, whether RBCs can move from the ventricles into the lymphatic system and if so, whether this process can be therapeutically stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of this drainage may offer therapeutic approaches to alleviate subarachnoid hemorrhage severity. 95 It is also shown that subdural hematoma was absorbed through the meningeal lymphatic vessel drainage pathway and that hematomas could inhibit the function of meningeal lymphatic vessels. 96 In the search for the T-cell gateways into and out of the meninges, functional lymphatic vessels lining the dural sinuses were discovered.…”
Section: Research On the Function Of Meningeal Lymphatic Vesselsmentioning
confidence: 99%
“…The midbrain close to the periaqueductal gray is implicated in the expression of autonomic nervous system activity via serotonergic neurons, which regulate the sleep/wake rhythm as well as mode and cognition. The cerebellum is one of the hottest regions newly known related to distinct psychiatric disorders: autism spectrum disorders (ASDs), schizophrenia, and mood disorders [ 10 , 29 , 30 , 31 ], although the cerebellum had been considered the central area of motor coordination, and cerebellar abnormalities were believed to exclusively induce coordination disorder and tremor [ 32 , 33 , 34 ]. Therefore, the view of aberrant immune-triggered psychiatric disorders should be noticed what brain regions are functionally disrupted and what connections of brain regions are impaired.…”
Section: Main Textmentioning
confidence: 99%
“…In the disease model, monocytic infiltration is observed with progression to paralytic stages of EAE [ 115 ]. Parenchymal microglia modulate the intrinsic excitability [ 10 , 29 , 118 ] and the efficacy of synaptic transmission [ 119 ] of CNS neurons. They also engulf dendritic spines via C1q complement signaling in the developmental and senile brain [ 120 , 121 ].…”
Section: Main Textmentioning
confidence: 99%